2016
DOI: 10.1107/s1600576716005331
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse X-ray scattering from 180° ferroelectric stripe domains: polarization-induced strain, period disorder and wall roughness

Abstract: A key element in ferroic materials is the presence of walls separating domains with different orientations of the order parameter. It is demonstrated that 180 stripe domains in ferroelectric films give rise to very distinct features in their diffuse X-ray scattering (DXS) intensity distributions. A model is developed that allows the determination of not only the domain period but also the period disorder, the thickness and roughness of the domain walls, and the strain induced by the rotation of the polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…We note that these observations differ from those of Fong et al 27 , who found that in ultrathin PbTiO 3 films, the diffuse scattering due to the periodic domain structure instead evolves from a uniform ring (F β phase) at lower temperatures to a structure with {100} DWs (F α phase) upon heating, accompanied by an abrupt decrease in the domain period. We also observe a gradual decrease in the domain period with temperature, but no abrupt changes, consistent with previous reports 28,29 . Our observations are also different from the abrupt change in the alignment of ferroelastic DWs observed on heating in BaTiO 3 thin films 30 .…”
Section: Resultssupporting
confidence: 92%
“…We note that these observations differ from those of Fong et al 27 , who found that in ultrathin PbTiO 3 films, the diffuse scattering due to the periodic domain structure instead evolves from a uniform ring (F β phase) at lower temperatures to a structure with {100} DWs (F α phase) upon heating, accompanied by an abrupt decrease in the domain period. We also observe a gradual decrease in the domain period with temperature, but no abrupt changes, consistent with previous reports 28,29 . Our observations are also different from the abrupt change in the alignment of ferroelastic DWs observed on heating in BaTiO 3 thin films 30 .…”
Section: Resultssupporting
confidence: 92%
“…5) showed the systematic disappearance of the skyrmion satellite peaks with increasing electric field, indicating field-induced structural changes related to the skyrmions ( ). The external electric field in the out-of-plane direction breaks the symmetry and tends to align the dipoles along the direction of the external field to minimize the energy 32,33 . The electric field-driven change in the size of the skyrmion directly impacts the effective dielectric permittivity as well as the negative component of permittivity (Supplementary Note 3, Extended Data Fig.…”
Section: Field-and Temperature-driven Permittivity and Topological Phmentioning
confidence: 99%
“…This possibility can be evaluated using the domain diffuse scattering intensities derived as a function of domainwall width. 33 Assuming that the domain wall width is zero in the SL nanostructure, the observed intensity enhancement occurs only when the domain wall width reaches 16 nm in the unpatterned region, which is an unphysically large value. [34][35] A final artifact would arise if the areas occupied by up and down polarizations within the nanodomain period were different in the SL nanostructure than in the unpatterned region.…”
Section: Resultsmentioning
confidence: 99%